واقع تطبيق محاسبة المسؤولية الاجتماعية في المصارف السودانية - Issa, Hassan Musa (Gezira Journal of Economic and Social Sciences; مجلد 11 عدد 2 (2020), 2022)
هدفت هذه الدراسة إلى الوقوف على واقع تطبيق محاسبة المسؤولية الاجتماعية في المصارف السودانية وذلك من خلال التعّرف على مدى إدراك إدارات هذه المصارف لمفهوم المسؤولية الاجتماعية ومدى وجود إدارة مستقلة بالمصرف تقوم بمهام المتابعة والإشراف على أنشطة وبرامج المسؤولية الاجتماعية إضافة إلى التعّرف على مجالات تطبيق محاسبة المسؤولية الاجتماعية في هذه المصارف. اتبعت الدراسة المنهج الوصفي التحليلي، وتم جميع البيانات عن طريق استبيان تم توزيعه على الإدارات (أعضاء مجلس الإدارة ومديري الإدارة المالية) بالمصارف السودانية. توصلت الدراسة لنتائج عديد أهمها أن إدارات المصارف السودانية تدرك جيداً مفهوم المسؤولية الاجتماعية، كما تبين أنّه لا يوجد بمعظم المصارف السودانية، وبنك السودان المركزي، قسم أو وحدة خاصة مسؤولة عن متابعة ورقابة والإشراف على برامج وأنشطة المسؤولية الاجتماعية، كذلك توصلت الدراسة إلى أن المصارف السودانية تطبق محاسبة المسؤولية الاجتماعية بدرجات متفاوتة، فقد جاء مجال المساهمين  والعملاء بدرجة عالية من التطبيق، بينما جاء التطبيق في مجالي البيئة والعاملين بدرجة ضعيفة جداً. أوصت الدراسة بضرورة إنشاء قسم أو وحدة خاصة مستقلة تتولى مهام متابعة ورقابة والإشراف على تنفيذ البرامج والأنشطة والمشروعات الاجتماعية، كما أوصت بزيادة الاهتمام بمجالي العاملين وحماية البيئة.  Abstract The Current application of Social Responsibility Accounting in the Sudanese Banks   Abstract The study aims to determine how far the Sudanese banks apply social responsibility accounting, through identifying the extent to which Sudanese banks managements, ( Board of  Directors and Financial Affairs Managements) recognize the concept of social responsibility and to detect where there is department or unit specialized and responsible for follow up ,control and supervision over the programs and activities of the social responsibility and finally determine the areas in which Sudanese banks apply Social responsibility accounting .The study adopted descriptive analytical methodology, to collect the date questionnaire was designed and handed out to the managers. The study arrived at a number of results, the most important of which are: the managers of Sudanese banks realize the concept of social responsibility; it was also clear that there is no department or unit specialized and responsible for follow up, control and supervision over the programs and activities of the social responsibility in either Sudanese banks or central bank of Sudan, it was also clear that there was different level of application of social responsibility accounting from one area to another, the banks apply social responsibility accounting regarding customers  and shareholders at an high level but the application was at an low level in the area of employs and environment protection. The study concluded with a number of recommendations, the most important of which were: the necessity of establishment of an independent department or an unit to undertake the tasks of control and supervision over the implementation of social programs, activities and projects; finally the study recommends the necessity of the concern with the areas of employ's and environment protection.